2014
DOI: 10.4081/aiua.2014.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders among robotic surgeons: A questionnaire analysis

Abstract: Objective: Robotic surgical systems offer better workplace in order to relieve surgeons from prolonged physical efforts and improve their surgical outcomes. However, robotic surgery could produce musculoskeletal disorders due to the prolonged sitting position of the operator, the fixed position of the console viewer and the movements of the limbs. Until today, no one study has been reported concerning the association between robotics and musculoskeletal pain. The aim of this work was verify the prevalence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Respondents’ most frequently reported symptoms were: discomfort in neck, shoulders, and (lower) back, which was in line with previous studies reporting on intraoperative adjustments and/or sick leave due to musculoskeletal complaints [7, 26, 29, 33, 41]. These localizations are in agreement with the posture during minimally invasive surgery.…”
Section: Discussionsupporting
confidence: 87%
“…Respondents’ most frequently reported symptoms were: discomfort in neck, shoulders, and (lower) back, which was in line with previous studies reporting on intraoperative adjustments and/or sick leave due to musculoskeletal complaints [7, 26, 29, 33, 41]. These localizations are in agreement with the posture during minimally invasive surgery.…”
Section: Discussionsupporting
confidence: 87%
“…Although the dry lab trial evaluation provided an objective evaluation of the developed retractor, subjective assessment by the surgeons themselves is equally important. 17,18 The questionnaire scores reflected equally positive results with regard to ease of use and overall satisfaction, further confirming the above expectation of improved surgical outcomes that will directly benefit the patient.…”
Section: Discussionsupporting
confidence: 66%
“…The two groups of doctors probably shared similar co-morbidities of obesity, hyperlipidemia, and cardiovascular disease. On the other hand, only a few studies have investigated the risk of spinal problems and other musculoskeletal disorders among different medical specialties [ 22 , 23 , 24 ]. One study which enrolled 94 cardiologists demonstrated that interventional electrophysiologists had a higher prevalence of spondylosis than non-interventional cardiologists.…”
Section: Discussionmentioning
confidence: 99%